The impact of opioid administration on the incidence of postanaesthetic colic in horses - Haralambus, Rhea; Juri, Michaela; Mokry, Anna; Jenner, Florien (Frontiers in Pain Research, 2024)
Effective management of postoperative pain is essential to ensure patient welfare, reduce morbidity and optimize recovery. Opioids are effective in managing moderate to severe pain in horses but concerns over their adverse effects on gastrointestinal (GI) motility and associated increased colic risk limit their widespread use. Studies investigating the impact of systemic opioids on both GI motility and colic incidence in horses have yielded inconclusive outcomes. Therefore, this retrospective study aims to assess the influence of systemic administration of butorphanol, morphine, and methadone on post-anaesthetic colic (PAC) incidence. Horses undergoing general anaesthesia for non-gastrointestinal procedures that were hospitalized for at least 72 h post-anaesthesia were included in this study. Anaesthetised horses were stratified by procedure type into horses undergoing diagnostic imaging without surgical intervention, emergency or elective surgery. In addition, patients were grouped by opioid treatment regime into horses receiving no opioids, intraanaesthetic, short- (<24 h) or long-term (>24 h) postoperative opioids. Administered opioids encompassed butorphanol, morphine and methadone. The number of horses showing signs of colic in the 72 h after anaesthesia was assessed for each group. A total of 782 horses were included, comprising 659 undergoing surgical procedures and 123 undergoing diagnostic imaging. The overall PAC incidence was 15.1%. Notably, horses undergoing diagnostic imaging without surgery had a significantly lower PAC rate of 6.5% compared to those undergoing surgery (16.7%, p = 0.0146). Emergency surgeries had a significantly lower PAC rate of 5.8% compared to elective procedures (18%, p = 0.0113). Of the 782 horses, 740 received intraoperative opioids and 204 postoperative opioids, 102 of which long-term (≥24 h). Neither intraoperative (p = 0.4243) nor short-term postoperative opioids (p = 0.5744) increased PAC rates. Notably, only the long-term (≥24 h) administration of morphine significantly increased PAC incidence to 34% (p = 0.0038). In contrast, long-term butorphanol (5.3% PAC, p = 0.8482) and methadone (18.4% PAC, p = 0.6161) did not affect PAC rates. In summary, extended morphine administration was the only opioid treatment associated with a significantly increased risk of PAC.